Formalisation and business development in Mozambique: how important are regulations ? - Matthias Krause; Moritz Ackermann; Lena Gayoso; Claudia Hirtbach; Martin Koppa; Lena Siciliano Brêtas (Deutsches Institut für Entwicklungspolitik (DIE), 2010)
In recent years the Doing Business reports from the World Bank and the International Finance Corporation have received a lot of attention within the debate among researchers and policy makers about how to support private sector development in developing countries. In a nutshell, the Doing Business reports advocate lessening business regulations in order to promote enterprise development – a position that is a matter of controversial discussion. This study contributes to enlarging the empirical evidence regarding the relevance of regulatory reforms in the Sub-Saharan African context. It analyses the influence of the regulatory business environment on the formalisation and development of micro, small and medium enterprises in Mozambique. Although the authors devote considerable attention to coming up with an understanding of the effects of the regulatory business environment, they also take a look at further factors that are likely to have an effect on formalisation and business development. This has helped them to assess the relevance of reforming the regulatory business environment in relation to other policy measures aiming at private sector development.
Keywords: 330